A comparative demo-geographic perspective of Covid-19 spread and measures in Slovenia with a special emphasis on regional disparities and border areas - Josipovič, Damir (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The article examines how the initial Covid-19 spread reached Slovenia, how the infections are distributed across the Slovenian regions, and what disparities can be traced in municipalities, especially along the Croatian and Austrian borders. Furthermore, it identifies the demographic groups most affected by the restrictive measures as well as by SARS-CoV-2 infections and Covid-19 deaths. The research hypothesis was that peripheral and border area populations, including ethnic minorities, in Slovenia suffer the Covid-19 restrictions the most. Employing interdisciplinary analyses, we conclude that the spread of Covid-19 in Slovenia and the imposed lockdowns to municipalities create new vulnerable groups and that the wholesale lockdown cannot deliver the desired results if oriented to broad populations without considering regional and local disparities.
Keywords: Avstrija; demografski kazalniki; interdisciplinarna raziskava; Italija; medicinska geografija; pandemija covid 19; Slovenija; slovensko-hrvaško obmejno območje; stopnja umrljivosti